Joker in the pack. (Economist, 2016)
This article presents scenarios if financial systems around the world were hacked. It discusses a warning made by a network of activists, called Anonymous, about its campaign against central banks' web sites across the world, the impact of cyber attacks on consumer trust in financial institutions, the vulnerabilities created by processes designed to improve safety of banks, and the growth in cyber attack on banks.